Houseflies of the Tristan da Cunha Islands: new records, including the first for Fannia albitarsis Stein, 1911 (Diptera: Fanniidae, Muscidae). - Hänel, Christine; Pont, Adrian C. (Contributions to Entomology = Beiträge zur Entomologie, 2008)
Information about the Fanniidae and Muscidae Houseflies of the south Atlantic island group of Tristan da Cunha, from the earliest records to the most recent findings, is presented and discussed. In total, five species belonging to four genera are recorded. This includes the finding for the first time of Fannia albitarsis Stein, 1911 in the archipelago and Muscina stabulans (Fallén, 1817) on Nightingale Island. Based on material collected in 2005 from the two northern islands, Tristan da Cunha and Nightingale, records and notes are given on four species. A discussion of the correct taxonomic rank of Coenosia trina Wiedemann, 1830 is given. The apparent proliferation of this species, and the possible implications that this may have on endemics, is noted. Keywords Diptera, Muscidae, Fanniidae, Housefly, Lesser Housefly, Stable fly, Tristan da Cunha, Nightingale, Gough, Inaccessible, Island, South Atlantic.